Some Physical Properties of the Grains of Two Cultivars of Sorghum (Sorghum bicolor (L.) Moench) (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted at the Department of AgriculturalEngineering, Faculty of Agriculture, University of Khartoum and theFood Processing Research Center, Shambat, Sudan. The study was carriedout with the objective of determining some physical properties of twolocal grain sorghum cultivars that affect design of processing machines,storage structures and processes. The studied of physical propertiesincluded grain size, shape, 1000 grain weight, hectoliter (test) weight,hardness, bulk density, true density and porosity. These properties weredetermined at initial moisture content and the results were analyzed usingthe t-test. The results showed that the the two cultivars were significantlydifferent in size, shape and hardness, while they were not significantlydifferent with respect to hectoliter (test) weight, 1000 grain weight, bulkdensity, true density and porosity. The studied cultivars of grain sorghumdo not require different designs of milling machines, grain hoppers,aeration, drying machines and storage structures, while they differ withrespect to design of sieve separators, harvesting, sizing, grindingmachines and in calculating surface area and volume of grains which areimportant during modeling of grain drying, heating and cooling processes
Keywords: physical properties of two grain sorghum cultivars